Increasing returns to scale and the long-run Phillips curve - Andrea Vaona; Dennis J. Snower (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2007)
A growing body of empirical evidence shows that there exists a long-run positive tradeoff between inflation and real macroeconomic activity. Within a New Keynesian framewok, we examine how increasing returns generate a positive long-run relation between inflation and output.
Keywords: E3; E20; E40; E50; 330; Phillips curve; inflation; increasing returns; nominal inertia; monetary policy